Impact of exercise on cardiovascular disease risk in overweight or obese children and adolescents: a systematic review and meta-analysis - Jie Men; Guoyu Zhu; Yishan Li; Simin Wu; Zhengyang Yu; Pengbo Wang; Yuxi Zhang; Weiqi An; Jingwen Wang; Xiaoli Huang; Yu Wu; Xinyu Hou (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The aim of this study was to systematically evaluate the effects of exercise on cardiovascular disease (CVD) risk factors in overweight and obese children and adolescents. Methods Two independent reviewers conducted a comprehensive search of databases, including PubMed, the Cochrane Library, Embase, Web of Science, CNKI, and Wan Fang, covering the period from January 1, 2008, to May 19, 2025. Eligible randomised controlled trials (RCTs) were included in the meta-analysis. Sensitivity analysis was used to assess the stability of the results. Publication bias was evaluated using funnel plots, and subgroup analyses were also performed. Results A total of 83 RCTs involving 5,172 overweight or obese children and adolescents were included. Participants ranged in age from 5 to 19 years, and intervention durations ranged from 8 to 48 weeks. Compared with controls, exercise significantly reduced levels of total cholesterol (TC, SMD = -0.70, 95% CI [-0.91, -0.49]), triglycerides (TG, SMD = -0.60, 95% CI [-0.79, -0.41]), low-density lipoprotein (LDL, SMD = -0.61, 95% CI [-0.79, -0.43]), fasting plasma glucose (FPG, SMD = -0.40, 95% CI [-0.57, -0.23]), and fasting insulin (FIN, SMD = -0.80, 95% CI [-1.08, -0.51]), while significantly increasing high-density lipoprotein (HDL, SMD = 0.38, 95% CI [0.22, 0.53]) levels. Subgroup analyses indicated that endurance training led to broader improvements than other exercise types, especially at doses of ≥ 50 min per session, ≥ 3 sessions per week, and ≥ 12 weeks in duration. Additionally, the effects were more pronounced in males and studies conducted in Asia. High heterogeneity was observed (I 2  > 75%), but sensitivity analyses confirmed the robustness of the results, and no significant publication bias was detected in the funnel plots. Conclusions Exercise effectively improves overweight, obesity, and CVD risk factors in children and adolescents. Moderate-to-high-intensity endurance training (≥ 50 min/session, ≥ 3 times/week, for ≥ 12 weeks) yields the most significant benefits. The intervention effects appear to be influenced by sex and geographic region. Further well-designed, high-quality longitudinal studies are warranted to optimise exercise-based intervention strategies.